2020
DOI: 10.3168/jds.2019-16911
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of liking for Cheddar cheese shreds

Abstract: The prepackaged cheese shred category has steadily increased over the past few years, and Cheddar shreds represent the highest volume in this category. Recent studies have established extrinsic attributes that drive purchase in this category, but no published studies have addressed the intrinsic flavor and texture properties that drive consumer liking. The objective of this study was to determine the desirable flavor and functional attributes for Cheddar cheese shreds. We conducted a category survey of commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…The Penalty Analysis applied to the liking data and the RATA responses clearly identified four sensory drivers of liking related to the ('sweet' and 'salty') taste, ('nutty') flavor, and ('creamy') mouthfeel. As it is well known that drivers of liking can vary as a function of different cheese types and clusters of consumers [12,42,49], our results are in agreement with the previous literature on cheese preferences. For instance, nutty, salty, and sweet were attributes positively correlated with the overall liking of Swiss cheese [50].…”
Section: Consumers' Perception Of the Gorgonzola Cheese Sensory Propertiessupporting
confidence: 92%
“…The Penalty Analysis applied to the liking data and the RATA responses clearly identified four sensory drivers of liking related to the ('sweet' and 'salty') taste, ('nutty') flavor, and ('creamy') mouthfeel. As it is well known that drivers of liking can vary as a function of different cheese types and clusters of consumers [12,42,49], our results are in agreement with the previous literature on cheese preferences. For instance, nutty, salty, and sweet were attributes positively correlated with the overall liking of Swiss cheese [50].…”
Section: Consumers' Perception Of the Gorgonzola Cheese Sensory Propertiessupporting
confidence: 92%
“…These results demonstrated that consumers could recognize differences among samples by having different overall liking scores, but they struggled to communicate what the perceived differences are. This result was expected and was consistent with a previous study done by Meals, Schiano, and Drake (2019) where consumers documented differences in liking of cheese shreds, but struggled with CATA selections of mild cheese flavors (e.g., milky, brothy, etc.) to describe different cheese shreds, but instead relied on basic tastes, texture and appearances.…”
Section: Consumer Acceptance Testingsupporting
confidence: 92%
“…Since it has been suggested that more than 1000 types of cheese exist [32] with very different characteristics [9], sensory drivers of liking will be specific to different types of cheese. Nonetheless, they are likely to encompass multiple sensory modalities (appearance, aroma, taste, flavour, texture, mouthfeel, and aftertaste) [20,21,[33][34][35]. This extends to cream cheese (PBCA and dairy) [18,22,36,37].…”
Section: Objectivementioning
confidence: 99%
“…Consumer segmentation based on product liking was expected to exist. Considering that individual differences in preference are described for many foods and beverages [49] including dairy-based cheese [21,33,50] and PB alternative foods [51][52][53], interest in the present research was centred on the relative size of segments that liked, rejected, or partially accepted PBCA. Such knowledge is relevant because it helps to determine the magnitude of the change that has to occur for the consumption of PB alternative foods to become the norm rather than the exception.…”
Section: Objectivementioning
confidence: 99%